Pemanfaatan Media Instagram Sebagai Media Promosi Ekowisata oleh Balai Taman Nasional Batang Gadis - Aksyah, Egenda (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
Indonesia is a very large unitary country and has many places that are still relatively remote but have millions of very beautiful natural beauties. The use of social media based on an internet connection as a communication medium in tourism is now becoming more flexible and profitable for all parties because the use of social media like this is considered easier to use and apply and has a very wide reach because it is not limited. space and time. Apart from that, the use of social media can also be said to be cost-effective for communicating various kinds of information about existing and even growing tourism places or sites. This research aims to examine and analyze the use of Instagram media as an ecotourism promotion media by the Batang Girls National Park Office. Batang Girls National Park is one of Indonesia's important ecotourism destinations, with its stunning natural beauty and extraordinary biodiversity. However, despite its great potential, challenges in promoting this national park to a wider audience still remain. In this research the theory used is Harold Laswell's theory. The method in this research uses qualitative methods by analyzing data, processing and drawing conclusions in a descriptive qualitative manner. The results of the research show that the Batang Girls National Park Center has succeeded in utilizing Instagram media as an effective promotional tool. Their Instagram account has succeeded in attracting potential visitors with interesting and informative content